Analisis Kinerja Keuangan Bank Umum Syariah di Indonesia Tahun 2022 dengan Pendekatan Maqasid Syariah Index (MSI) - Dinda Rusmayani Utami (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research analyzes the financial performance of Islamic Commercial Banks (Bank Umum Syariah) in Indonesia during 2022 using the Maqasid Shariah Index (MSI) framework. The MSI method, rooted in Islamic jurisprudence, evaluates bank performance in line with three objectives of Shariah: education, justice, and welfare. This study involves six major Islamic banks: Bank Syariah Indonesia, Bank Muamalat Indonesia, BCA Syariah, Aladin Syariah, Syariah Bukopin, and Mega Syariah. Data from annual reports and secondary sources were analyzed using the Simple Additive Weighting (SAW) method, assessing ten key financial ratios corresponding to Maqasid Shariah principles. The findings suggest that despite challenges in 2022, banks achieved variable success in different Shariah goals, with recommendations to enhance educational contributions and promote justice to improve overall performance. These insights offer valuable considerations for future regulation and development of Islamic banking in Indonesia.